Enriching Physics Education with Islamic Heritage: Al-Khazini’s Gravitational Theory - Flara, Riana Lady; Irawan, Irawan; Rahim, Faszly; Nuryantini, Ade Yeti; Agustina, Tri Wahyu (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
This research examines the contributions of Al-Khazini, a 12th-century Muslim scientist, who proposed the theory of gravity in his book “Mizan Al-Hikmah,” predating Isaac Newton by several centuries. Despite Al-Khazini’s pioneering work, his contributions are often overlooked in the history of Physics, with Newton predominantly recognized in educational contexts. This study aims to underscore Al-Khazini’s significant role in the development of gravitational theory and enhance students’ understanding of the history of Physics. Employing a qualitative descriptive approach and literature review, the research analyzes relevant references to highlight this oversight. This study found that Physicsteachers frequently omit the discoveries of Muslim scientists, leading to a Western-centric view of Physicshistory among students. The study concludes that while Al-Khazini first conceptualized the theory of gravity, Newton later formulated it mathematically. Integrating Al-Khazini’s contributions into Physicseducation can enrich students’ comprehension of scientific history, deepen their grasp of gravitational concepts, and foster appreciation for the contributions of Muslim scientists. This integration promotes a more diverse and inclusive teaching approach, encouraging curriculum revisions to better acknowledge Islamic intellectual heritage and provide a more comprehensive education.